2014
DOI: 10.4238/2014.april.29.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secondary lymphoid tissue chemokine suppression on experimental ulcerative colitis in mice

Abstract: ABSTRACT. The secondary lymphoid tissue chemokine (CCL21) is closely associated with lymphoid homing and anti-tumor immune responses. CCL21 also has a chemotactic effect on intestinal lymphocytes. This study mainly focused on CCL21 expression in experimental ulcerative colitis and on the effects of CCL21 suppression on this disease in mice. The mouse colitis model was induced by dextran sulfate sodium (DSS) in 40 female BALB/c mice that were equally distributed into five groups: control, DSS, propylene glycol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Li et al (2010) found that triptolide ameliorates colitis by suppressing the IL-6/signal transducer and activator of transcription 3 (STAT3) signaling pathway and downregulating IL-17. Zhang et al (2014) found that 0.6 mg/kg/day triptolide administration ameliorates intestinal injury by inhibiting the expression of secondary lymphoid tissue chemokine chemokine (C-C motif) ligand 21 (CCL21), which has chemotactic effects on T cells, B cells, NK cells, and DCs. However, they only investigated the expression of CCL21, which is not sufficient to demonstrate triptolide influence the chemotactic effects of T cells, B cells, NK cells, and DCs.…”
Section: Potential Effects Of Triptolide On Inflammatory Diseasesmentioning
confidence: 99%
“…Li et al (2010) found that triptolide ameliorates colitis by suppressing the IL-6/signal transducer and activator of transcription 3 (STAT3) signaling pathway and downregulating IL-17. Zhang et al (2014) found that 0.6 mg/kg/day triptolide administration ameliorates intestinal injury by inhibiting the expression of secondary lymphoid tissue chemokine chemokine (C-C motif) ligand 21 (CCL21), which has chemotactic effects on T cells, B cells, NK cells, and DCs. However, they only investigated the expression of CCL21, which is not sufficient to demonstrate triptolide influence the chemotactic effects of T cells, B cells, NK cells, and DCs.…”
Section: Potential Effects Of Triptolide On Inflammatory Diseasesmentioning
confidence: 99%
“…By comparing the effect of TL and dexamethasone on a mouse model of DSS-induced ulcerative colitis, the authors of the present study have previously indicated that TL may alleviate the symptoms of UC in the colons of mice by downregulating the expression of secondary lymphoid tissue chemokine, implying that TL may execute its therapeutic effect on UC by inhibiting the overexpression of secondary lymphoid tissue chemokine (37). …”
Section: Discussionmentioning
confidence: 77%
“…of inflammatory bowel diseases by selectively interfering with recruitment of naïve immune effector cells to sites of antigen presentation, without harming overall memory immunity [16][17][18][19].…”
Section: Plos Onementioning
confidence: 99%
“…While progress has been made, changing the natural history of inflammatory bowel diseases (IBD) is still problematic because the initiators of the disease are imperfectly defined [16,17]. The goal of interrupting the signaling cascade that leads to the destruction of the intestinal mucosa in these diseases has been hampered not just by the lack of targets but by the ineffectiveness of therapies against the targets that are known [5,8,[16][17][18][19]. Since the gut is its own secondary lymphoid organ where naïve lymphocytes can be presented antigen locally instead of maturing in a secondary lymphoid organ and then migrating to target inflamed/infected tissues, one potential IBD therapeutic target could be interrupting the migration of naïve lymphoid cells into the inflamed gut [5,7,8,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation